DEVELOPMENT OF A DIAGNOSTIC INDEX FOR ASSESSING OCCUPATIONAL SAFETY CULTURE IN CONSTRUCTION ENTERPRISES - E. M.Murtazaev; B. E.Mustafayev (Web of Journals Publishing, 2025)
Ensuring a high level of occupational safety culture is essential for minimizing workplace accidents in construction enterprises, which remain among the most hazardous sectors worldwide. This study aims to develop a comprehensive Diagnostic Index of Safety Culture (DISC) for evaluating the maturity level of safety culture within construction organizations. A mixed-method approach was employed, combining a systematic literature review, expert evaluation using the Delphi method, and statistical validation through exploratory and confirmatory factor analysis (EFA/CFA). The DISC model consists of five core dimensions—management commitment, employee competence, communication efficiency, risk control practices, and safety behaviour indicators—measured through 31 validated criteria. Reliability testing showed high internal consistency (Cronbach’s α = 0.89), while CFA confirmed strong model fit (CFI = 0.94; RMSEA = 0.05). The developed index enables construction firms to diagnose weaknesses, track cultural improvements, and implement evidence-based safety programs. Practical implications include its integration into corporate safety audits and digital monitoring systems. Future research may extend the index through machine-learning-based predictive analytics.
Keywords: Safety culture, diagnostic index, construction industry, occupational safety, risk management, safety audit.